A 1500-year record of North Atlantic storm flooding from lacustrine sediments, Shetland Islands (UK) - Heß, Katharina; Engel, Max; Patel, Tasnim; Vakhrameeva, Polina; Koutsodendris, Andreas; Klemt, Eckehard; Hansteen, Thor; Kempf, Philipp; Dawson, Sue; Schön, Isa; Heyvaert, Vanessa M. A. (Journal of quaternary science, 2024)
Severe storm flooding poses a major hazard to the coasts of north-western Europe. However, the long-term recurrence patterns of extreme coastal flooding and their governing factors are poorly understood. Therefore, high-resolution sedimentary records of past North Atlantic storm flooding are required. This multi-proxy study reconstructs storm-induced overwash processes from coastal lake sediments on the Shetland Islands using grain-size and geochemical data, and the re-analysis of historical data. The chronostratigraphy is based on Bayesian age-depth modelling using accelerator mass spectrometry 14C and 137Cs data. A high XRF-based Si/Ti ratio and the unimodal grain-size distribution link the sand layers to the beach and thus storm-induced overwash events. Periods with more frequent storm flooding occurred 980-1050, 1150-1300, 1450-1550, 1820-1900 and 1950-2000 ce, which is largely consistent with a positive North Atlantic Oscillation mode. The Little Ice Age (1400-1850 ce) shows a gap of major sand layers suggesting a southward shift of storm tracks and a seasonal variance with more storm floods in spring and autumn. Warmer phases shifted winter storm tracks towards the north-east Atlantic, indicating a possible trend for future storm-track changes and increased storm flooding in the northern North Sea region.
Online veröffentlicht: 21. September 2023
Gesehen am 07.12.2023